Correlation between placental pathology and neonatal morbidity: a case-control study - Kornete, Anna; Vedmedovska, Natalija; Blazuka, Solvita (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Preterm births occur in approximately 12% of pregnancies worldwide and in 5.6% of pregnancies in Latvia, and the incidence has increased. Prematurity poses the major challenge in perinatology and pediatrics, accounting for 75% of perinatal mortalities and 50% of long-term complication. The placenta is a unique organ in explaining the incomprehensible pathogenesis of prematurity. Methods: The retrospective case-control study was conducted to determine placental histological and microbiological findings associated with gestational age and neonatal morbidity. Results: Histological chorioamnionitis was the most prevalent lesion in extremely preterm and very preterm birth groups compared with moderate to late preterm and term birth groups (P=0.027). A higher rate of funisitis was detected among extremely preterm and very preterm birth cases (P=0.001). Microbiological examination of placentas in preterm birth cases most commonly revealed Streptococcus agalactiae, Staphylococcus epidermidis, Staphylococcus haemolyticus. Umbilical cord vessels thrombosis and placental thrombotic vasculopathy were found mostly in moderate to late preterm birth category (P=0.032; P=0.008, respectively). Intrauterine growth restriction was linked to chorionic villous edema (P=0.007) and chorionic villous fibrinoid necrosis (P=0.014). Chorion-decidual hemorrhage and deciduitis were significantly associated with respiratory distress syndrome (P=0.036; P=0.022, respectively). Chorion-decidual hemorrhage was the main predisposing factor for hypoxic-ischemic encephalopathy (P=0.058). Conclusions: Comprehension of the pathogenic mechanisms of prematurity of the placenta and preterm births, and the impact of placental prematurity on neonatal morbidity may lead to improved prenatal diagnostic and enhanced preventive care for both the mother and the child.